Solubility and Dissolution Enhancement of Poorly Water-soluble Ketoprofen by Microwave-assisted Bionanocomposites: In Vitro and In Vivo Study (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: Dissolution and diffusion through gastrointestinal membrane are the mechanisms by which drug get absorbed on oral route of administration. The major challenge in case of the majority of drugs is poor water solubility. Hence, the objective of the present study is to develop bionanocomposites (BNCs) by microwave-induced diffusion technique (MIND) to enhance solubility and dissolution of poorly water-soluble drug ketoprofen (KE). Materials and Methods: Natural drug carriers, ghatti gum, and acacia were selected for BNCs preparation based on their wetting and surface active agent property. BNCs were prepared by MIND method and characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction studies, scanning electron microscopy, and transmission electron microscopy. The solubility and dissolution enhancing performance of BNCs were assessed by In vitro solubility and dissolution studies. Carrageenan-induced rat paw edema model was performed to evaluate in vivo presentation of optimized KE formulation. Results and Discussion: It was demonstrated that dissolution of KE enhanced with increase in polymer attention. The optimized ratio of drug and polymer for the entire composite was found to be 1:3. The optimized formulation showed a significant reduction in rat paw edema as compared to marketed KE formulation. Conclusion: The study showed good in vitro and in vivo relationship. The MIND technique employed in this study is green and cost-effective method for bionanocomposites arrangement. Enhancement in the solubility might be because of generation of drug dispersion at micro- and nano-scale level. Hence, the development of BNCs is a promising approach to increase solubility and dissolution of poorly water-soluble drug.